2013
DOI: 10.1155/2013/737392
|View full text |Cite
|
Sign up to set email alerts
|

The Cohesive Zone Model for Fatigue Crack Growth

Abstract: In the past decade, the cohesive zone model has been receiving increasing attention as a powerful tool for the simulation of fatigue crack growth. When applying cohesive zone model to fatigue fracture problem, three aspects should generally be taken into account, that is, unloading-reloading path, damage evolution during cyclic loading, and crack surface contact and friction behavior. This paper addresses the critical views of these aspects. Before that, the formulation of cohesive zone model and identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…From the results shown in Figures 11 and 12, it can be concluded that any value higher than 6 for the updates parameter N u provides satisfactory results with a significant reduction in computational cost. It is clear from Figure 11 that the predicted results are reasonably close to each other for values of N u set to (56,28,14,7), which correspond to ΔN ≈ (100, 200, 400, 800), respectively. Differences are more noticeable however for values of N u lower than 6, where N u = 3 corresponds to ΔN≈2000 and N u = 1 corresponding to ΔN≈5600, as shown in Figure 12.…”
Section: Fast-track Effect On Accuracy Of the Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…From the results shown in Figures 11 and 12, it can be concluded that any value higher than 6 for the updates parameter N u provides satisfactory results with a significant reduction in computational cost. It is clear from Figure 11 that the predicted results are reasonably close to each other for values of N u set to (56,28,14,7), which correspond to ΔN ≈ (100, 200, 400, 800), respectively. Differences are more noticeable however for values of N u lower than 6, where N u = 3 corresponds to ΔN≈2000 and N u = 1 corresponding to ΔN≈5600, as shown in Figure 12.…”
Section: Fast-track Effect On Accuracy Of the Resultsmentioning
confidence: 54%
“…This permits the modelling of advanced behaviour at the cohesive interface and surroundings taking into consideration such things as friction and plasticity . Loading‐unloading hysteresis models are based on the reduction of the interfacial stiffness captured by a cyclic damage variable that evolves or an internal variable that grows; a review of CZMs for fatigue can be found in references herein . The first successful attempt to use a CZM for the simulation of fatigue crack growth is presented in De‐Andrés et al, which introduces a cyclic damage variable D , whose purpose is to quantify the amount of dissipated energy in the fracture process divided by the critical fracture energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 During the past decades, a vast number of CZM have been developed and published. We refer in this context to the review articles, 4,8,[13][14][15] where many aspects of CZ modeling are summarized and compared. Within the present study, however, the particular choice of the cohesive law is of less importance.…”
Section: 1mentioning
confidence: 99%
“…A wealth of literature on the modeling of delamination damage in FRPs have already existed; only a selection of recent pertinent ones will be reviewed here. Readers are referred to (Hutchinson 1982, Wisnom 2012, Liu et al 2013, Park and Paulino 2013 for a more complete review on recent developments in cohesive modeling methodologies. Different approaches are followed to simulate delamination in composites, and they can be broadly classified into three categories, viz.…”
Section: Introductionmentioning
confidence: 99%